2019
DOI: 10.1111/jep.13225
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and quality appraisal of bereavement care practice guidelines

Abstract: Bereavement care practice guidelines assist in delivering high-quality bereavement care. However, the quality of published guidelines is unknown. A systematic review was conducted to identify and evaluate the quality of the process used to develop bereavement care practice guidelines using the Appraisal of Guidelines for Research and Evaluation (AGREE II) instrument. A keyword search was conducted in MEDLINE-Complete, CINAHL-Complete, Health-Source (Nursing/Academic Edition), Psychology and Behavioral Sciences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…This might due to the insufficient collection of patients' views and preferences during guideline development. Similar suboptimal reporting on stakeholder involvement was documented from previous literatures (29)(30)(31). Although for physicians and surgeons, such information may have little role on the reliability of recommendation, the adoption of patients' opinions may be helpful to improve the informed decision for guideline development.…”
Section: Discussionsupporting
confidence: 52%
“…This might due to the insufficient collection of patients' views and preferences during guideline development. Similar suboptimal reporting on stakeholder involvement was documented from previous literatures (29)(30)(31). Although for physicians and surgeons, such information may have little role on the reliability of recommendation, the adoption of patients' opinions may be helpful to improve the informed decision for guideline development.…”
Section: Discussionsupporting
confidence: 52%
“…If unavailable, standards of care remain unclear, with health professionals lacking guidance on how to provide family care. Hence, there is a clear need to develop clinical practice guidelines for family engagement and support during the dying phase and the bereavement phase that are of high quality and implementable across settings (Kent et al, 2020;Sarkies et al, 2022;Spoon et al, 2020).…”
Section: Adoption Of and Barriers To Evidence-based Practicesmentioning
confidence: 99%
“…In fact, Molino et al showed that higher quality CPGs had reported funding sources 10 times more often than those of lower quality 24 . Multiple recent studies rea rmed the low scores across guidelines for this domain [59][60][61] ; and this gap is crucial in LMICs especially 62 , however, it can be argued that it is equally important for countries world-wide.…”
Section: Agree Tool Use and Domainsmentioning
confidence: 99%